Serious Game Controlled by a Human-Computer Interface for Upper Limb Motor Rehabilitation: A Feasibility Study - Pulido, sergio David; Bocanegra, Álavaro José; Cancino, Sandra Liliana; López, Juan Manuel (Springer, 2019)
Stroke affects the population worldwide, with a prevalence of 0.58% worldwide. One of the possible consequences is the negative impact in the motor function of the patient, limiting their quality of life. For these reason, Brain-Computer Interfaces are studied as a tool for improving rehabilitation processes. Nevertheless, to the best of our knowledge, there are no Brain-Computer Interface systems which use video-games for upper limb motor rehabilitation. This study aimed to design and assess a Human-Computer Interface that includes electroencephalography, forearm motion and postural analysis, with healthy subjects. This assessment was made by designing two scenarios in which the participant carried out exercises involving the mouth and the hand and forearm trajectory symmetry. Results show that the system is ready to be tested on patients, since the participants were comfortable using it. Also, the quantitative results, particularly, the metrics used in the video-game, are an important start for health professionals to characterize motor rehabilitation in stroke patients, enabling the path to the use of the designed system in motor rehabilitation therapies.

El ictus afecta a la población mundial, con una prevalencia del 0,58% a nivel mundial. Una de las posibles consecuencias es la negativa. impacto en la función motora del paciente, limitando su calidad de vida. Por este motivo, las Interfaces Cerebro-Computadora se estudian como una herramienta para mejorar los procesos de rehabilitación. Sin embargo, a nuestro mejor saber y entender conocimiento, no existen sistemas de interfaz cerebro-computadora que utilicen Videojuegos para la rehabilitación motora de miembros superiores. Este estudio tuvo como objetivo diseñar y evaluar una Interfaz Humano-Computadora que incluya electroencefalografía, movimiento del antebrazo y análisis postural, con sujetos sanos. Esta evaluación se realizó mediante el diseño de dos escenarios en los que el participante realizó ejercicios que involucran la boca y la mano y simetría de la trayectoria del antebrazo. Los resultados muestran que el sistema está listo para ser probado en pacientes, ya que los participantes se sentían cómodos usando él. Además, los resultados cuantitativos, particularmente, las métricas utilizadas en el videojuego, son un importante punto de partida para que los profesionales de la salud caractericen la rehabilitación motora en pacientes con accidente cerebrovascular, abriendo el camino hacia el uso del sistema diseñado en terapias de rehabilitación motora.
Keywords: Rehabilitación médica; Medical rehabilitation; Robótica médica; Robotics in medicine; Electroencefalografía; Electroencephalography; Actividad motora; Motor activity; Enfermedad cerebrovascular - Rehabilitación; Cerebrovascular disease - Rehabilitation; Human-Computer Interface; Interfaz hombre-computadora; Motor rehabilitation; Rehabilitación motora; Stroke; Ictus; Serious games; Juegos serios